2020
DOI: 10.1155/2020/9185041
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: The Case of Three Patients with the Same Diagnosis but Different Clinical and Laboratory Features

Abstract: SARS-CoV-2 is an RNA virus that causes COVID-19, which has been responsible for the pandemic that was declared in early 2020. Its pathological effect is majorly in the respiratory tract, but its full pathogenicity remains a mystery. Symptoms associated with COVID-19 include fever, cough, and shortness of breath. Some patients develop other symptoms like diarrhea. However, it is possible for other organs to be affected including the central nervous system, liver, and blood cells. The purpose of this case series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The trans-synaptic viral transfer is reported for other CoVs clathrin-dependent endocytotic/exocytotic pathway. Although SARS-CoV-2 enters through BBB in Nervous system, interestingly except one case study [11] all tested SARS-CoV-2 PCR in CSF was negative in our review [5,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Diminished viral RNA in the brain in autopsy studies (7 out of 22) of SARS-CoV-2 related fatality is suggestive of it [47].…”
Section: Sars-cov-2 and Neuroinvasionmentioning
confidence: 63%
See 3 more Smart Citations
“…The trans-synaptic viral transfer is reported for other CoVs clathrin-dependent endocytotic/exocytotic pathway. Although SARS-CoV-2 enters through BBB in Nervous system, interestingly except one case study [11] all tested SARS-CoV-2 PCR in CSF was negative in our review [5,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Diminished viral RNA in the brain in autopsy studies (7 out of 22) of SARS-CoV-2 related fatality is suggestive of it [47].…”
Section: Sars-cov-2 and Neuroinvasionmentioning
confidence: 63%
“…Among these articles, 12 were case reports; four were case series, and one study was a multicentre crosssectional study. Table-1 and Table-2 shows the summary of the included studies [5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. All studies were critically analyzed based on the standard diagnosis for epilepsy (e.g., EEG, head CT /MRI, CSF analysis).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…percent, rhinorrhoea was at 4 percent, chest pain was at 2 percent, diarrhoea was at 2 percent, and nausea and vomiting was at 1 percent.A study by Atere, et al showed that a dry cough, chest pain and dyspnoea were prominent in patients with lower respiratory tract symptoms on admission[3]. Other types of diagnosis for admission in a study by Willie and Motsepe included unspecified acute lower respiratory infection, other viral pneumonia, Adult respiratory distress syndrome, Bronchopneumonia, unspecified -Gastroenteritis, and colitis of unspecified origin[1].…”
mentioning
confidence: 99%